Role of peptidoglycan subtypes in the pathogenesis of bacterial cell wall arthritis. Issue 10 (12th September 2003) - Šimelyte, E; Rimpiläinen, M; Zhang, X; Toivanen, P
Abstract : Background: Bacterial cell wall (CW) arthritis develops in susceptible strains of rats after a single intraperitoneal injection of the CW from certain bacterial species, both pathogenic and non-pathogenic. For the development of chronic bacterial CW arthritis, the structure of the bacterial peptidoglycan (PG) has been found to be decisive. Objective: To define the role of PG subtypes in the pathogenesis of chronic bacterial CW arthritis. Method: Arthritis was induced with CWs of Lactobacillus plantarum, L casei B, L casei C, and L fermentum . Gas chromatography-mass spectrometry was used to measure the presence of CW derived muramic acid in the liver and to determine PG subtypes. CWs were also tested for their resistance to lysozyme in vitro. Results: These results and those published previously indicate that PGs of CWs which induce chronic arthritis, no matter whether they were derived from strains of Streptococcus, Bifidobacterium, Collinsella, or Lactobacillus, all have lysine as the third amino acid of the PG stem peptide, representing PG subtypes A3α and A4α. Those strains which induce only transient acute arthritis or no arthritis at all do not have lysine in this position, resulting in different PG subtypes. Conclusions: In vivo degradation of only those PGs with the subtypes A3α and A4α leads to the occurrence of large CW fragments, which persist in tissue and have good proinflammatory ability. CWs with other PG subtypes, even if they are lysozyme resistant, do not cause chronic arthritis, because the released fragments are not phlogistic. It is emphasised that a variety of microbial components not causing inflammation have been found in animal and human synovial tissue.